2000
DOI: 10.1097/00000539-200005000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia for Outpatient Arthroscopic Knee Surgery with Intraarticular Clonidine and/or Morphine

Abstract: Both clonidine, an alpha(2) agonist, and morphine, an opioid agonist, provide enhanced patient analgesia after arthroscopic knee surgery when administered via the intraarticular (IA) route. Clonidine potentiates morphine analgesia in the animal model. We designed this study to determine whether clonidine or morphine results in better analgesia and whether their combination would provide superior analgesia to either drug alone. We evaluated 60 patients undergoing arthroscopic knee meniscus repair under local an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 12 publications
2
44
0
5
Order By: Relevance
“…In humans undergoing arthroscopy, the relief of pain using intra-articular (IA) administration of  2 -agonists, opioids and local anaesthetics has been highly successful (Joshi et al, 2000;Elhakim et al, 1999). In particular, there are reports in the literature that effective analgesia follows an IA administration of lidocaine (Dahl et al, 1990;Arai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In humans undergoing arthroscopy, the relief of pain using intra-articular (IA) administration of  2 -agonists, opioids and local anaesthetics has been highly successful (Joshi et al, 2000;Elhakim et al, 1999). In particular, there are reports in the literature that effective analgesia follows an IA administration of lidocaine (Dahl et al, 1990;Arai et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Morphine, a narcotic analgesic, is used frequently and administered intravenously, 1) epidurally, 2) subarachnoidally, 3) subcutaneously, 4) and intramuscularly. 5) Continuous intravenous injection of morphine by patient-controlled analgesia (PCA) is often used in many countries and rated favorably.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Joshi and colleagues, 27 the mean time to first analgesic request after knee arthroscopy was 280 min after IA bupivacaine, 600 min after IA clonidine, 720 min after IA bupivacaine and morphine and 950 min after combined IA clonidine, bupivacaine and morphine. Al-Metwalli et al 5 concluded that IA dexmedetomidine alone provided around 312 min mean time of postoperative analgesia after knee arthroscopy.…”
Section: Discussionmentioning
confidence: 94%